Trigger Event meets Culture Shock: Linking the Literature of Transformative Learning Theory and Cross-Cultural Adaptation - Carol R. Lyon (Adult Education Research Conference, 2002)
The purpose of this exploration was to identify the links between the literature bases of transformative learning theory and cross cultural adaptation. Eight extant studies combining these two areas of literature were examined to find similarities and differences.